2022
DOI: 10.21203/rs.3.rs-1917087/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-genome sequencing of Pseudomonas koreensis isolated from diseased Tor tambroides

Abstract: BackgroundPseudomonas koreensis have been reported as a pathogen in freshwater fish. Unlike environmental P. koreensis from soil, which has been studied extensively for its role in promoting plant growth, pathogenic P. koreensis from fish has been assessed only to a very limited extent. This is the first draft genome of P. koreensis CM-01 isolated from the internal organs of diseased Tor tambroides.ResultsHerein, we report the morphological and biochemical characteristics, as well as whole genome sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…The presence of multiple fimbriae genes associated with type I fimbriae and type IV pili indicated that EOBSR_19 was likely able to adhere to and colonize a rather wide range of hosts or environments. Similar genes are also reported earlier in other strains, including E. roggenkampii ED5 (Guo et al., 2020), E. cloacae ATCC13047 (Liu et al., 2013), Vibrio parahaemolyticus TJA114 (Zhang et al., 2021), Pseudomonas koreensis CM‐01 (Kho et al., 2023), and Aeromonas veronii A8‐AHP (Tyagi et al., 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of multiple fimbriae genes associated with type I fimbriae and type IV pili indicated that EOBSR_19 was likely able to adhere to and colonize a rather wide range of hosts or environments. Similar genes are also reported earlier in other strains, including E. roggenkampii ED5 (Guo et al., 2020), E. cloacae ATCC13047 (Liu et al., 2013), Vibrio parahaemolyticus TJA114 (Zhang et al., 2021), Pseudomonas koreensis CM‐01 (Kho et al., 2023), and Aeromonas veronii A8‐AHP (Tyagi et al., 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Some of the efflux pump showed resistance activity in response to pathogenic bacterium that have been previously reported to P. koreensis CM‐01 (Kho et al., 2023) and A. veronii JC529 (Sheng et al., 2021). AcrAB‐TolC is a resistance‐nodulation‐cell division (RND) multiple drug efflux pump complex and it mediates the resistance against fluoroquinolone and tetracycline antibiotics, which is essential for intrinsic bacterial antibiotic resistance (Andersen et al., 2015; Hocquet et al., 2003; Li et al., 2015; Masuda et al., 2000; Swick et al., 2011).…”
Section: Discussionmentioning
confidence: 74%